2022
DOI: 10.1039/d2qo00167e
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective synthesis of 1,1,3,3-tetrasubstituted cyclobutanes enabled by cycloaddition of bicyclo[1.1.0]butanes

Abstract: A diastereoselective cycloaddition of bicyclo[1.1.0]butanes (BCBs) with triazolinedione or nitrosoarenes was developed to access multi-substituted cyclobutanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…To move beyond strictly carbocyclic isosteres (whose benets of higher C sp 3 may be countered by their high clog P), Leitch and co-workers explored if BCBs could be progenitors to 2-azabicyclo[2.1.1]hexanes (aza-BCHs) through a reaction with imines (Scheme 13). 116 This hypothesis expands on the reports in the early 1980s by Amey and Dougherty, 102,103 as well as the more recent work of Lu, 27 who found that BCBs undergo strainrelieving cycloadditions upon irradiation with 1,2,4-triazoline-3,5-diones. The latter have been recently been popularized by Sarlah for dearomative cycloaddition reactions and utilized for the aforementioned bioconjugation reported by Malins.…”
Section: Chemical Sciencesupporting
confidence: 71%
See 2 more Smart Citations
“…To move beyond strictly carbocyclic isosteres (whose benets of higher C sp 3 may be countered by their high clog P), Leitch and co-workers explored if BCBs could be progenitors to 2-azabicyclo[2.1.1]hexanes (aza-BCHs) through a reaction with imines (Scheme 13). 116 This hypothesis expands on the reports in the early 1980s by Amey and Dougherty, 102,103 as well as the more recent work of Lu, 27 who found that BCBs undergo strainrelieving cycloadditions upon irradiation with 1,2,4-triazoline-3,5-diones. The latter have been recently been popularized by Sarlah for dearomative cycloaddition reactions and utilized for the aforementioned bioconjugation reported by Malins.…”
Section: Chemical Sciencesupporting
confidence: 71%
“…3,26 This C-C bond is known to react with a wide variety of electrophiles and nucleophiles, in processes ranging from solvolysis-type reactions to the addition of "hard" organometallic nucleophiles 3 and a variety of thermal and photochemical cycloadditions. 3,27 This bond has also been shown to react in tandem with bridgehead aryl groups as part of a conjugated system. 28 The reactivity of the central C-C bond in BCB has also been leveraged in the development of cyclobutane-containing polymers formed by free-radical or anionic ring-opening of the corresponding BCB monomers (Scheme 1C).…”
Section: Properties and Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…1,1,3,3-Tetrasubstituted cyclobutene 190 , which is a potential precursor of achiral bis-amino acid 191 , was diastereoselectively synthesized by the cycloaddition of bicyclo[1.1.0]butanes 188 with triazolinedione 189 (Scheme 25). 55 Compared to C 2 -symmetric and meso bis-amino acid derivatives, there are fewer reports on the synthesis of bis-amino acids without chiral centres.…”
Section: Synthesis Of Symmetric Amino Acid Derivativesmentioning
confidence: 99%
“…For cross-linking by carbon chains, trimerization of a protected ( S )-tryptophan 192 with triethyl orthoformate has been reported (Scheme 26). 55 Although the synthesis of heterocyclic trimerization is beyond the scope of this review, the optically active 194 and 195 have been also synthesized (Fig. 4).…”
Section: Synthesis Of Symmetric Amino Acid Derivativesmentioning
confidence: 99%